2022
DOI: 10.1016/j.iref.2021.12.013
|View full text |Cite
|
Sign up to set email alerts
|

ESG scores and the response of the S&P 1500 to monetary and fiscal policy during the Covid-19 pandemic

Abstract: Examining the S&P 1500 stocks, the responses of the stocks to fiscal and monetary policy are found to differ due to E, S and G scores by the type of legislation. Non-Financial firms that manage environmental and governance risks better performed better over the pandemic. Part of this was due to their high environmental and governance scores allowing them to hedge the negative effects of the announcements of fiscal policies during the pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 26 publications
(22 reference statements)
1
15
0
Order By: Relevance
“…Table 9 also suggests that while the social factor in the ESG ratings is positively linked to systemic risk contribution and exposure, the governance/economic factor is negatively related. The latter is in line with the findings of Gregory (2022) that during the pandemic, non-financial firms with higher governance scores performed better. The coefficients are not very large, but for a 40-point improvement in these factors, the effect is 3.25% and −3.35%, respectively.…”
Section: Ols Regressions For 2020supporting
confidence: 90%
See 1 more Smart Citation
“…Table 9 also suggests that while the social factor in the ESG ratings is positively linked to systemic risk contribution and exposure, the governance/economic factor is negatively related. The latter is in line with the findings of Gregory (2022) that during the pandemic, non-financial firms with higher governance scores performed better. The coefficients are not very large, but for a 40-point improvement in these factors, the effect is 3.25% and −3.35%, respectively.…”
Section: Ols Regressions For 2020supporting
confidence: 90%
“…However, if firms have larger financial constraints, they may tend to hide unfavourable news and hence this effect is suppressed. Gregory (2022) analyses the S&P 1500 stocks and shows that the non-financial firms which had better environment and governance scores performed better throughout the COVID-19 pandemic. Sonnenberger and Weiss (2021) focus on the insurance firms and find that engaging in corporate social responsibility reduces tail risk and short and medium term exposure to systemic risk.…”
Section: Sustainability and Systemic Riskmentioning
confidence: 99%
“…Firm Size is measured by the natural logarithm of total assets (Lin et al, 2019). Leverage using debt to equity ratio (Gregory, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…, 2021; El Khoury et al. , 2021; Gregory, 2022). Second, since it is suggested that ESG may mitigate the negative impact of the COVID-19 pandemic on bank profitability (i.e., ROA) differently across subsamples [9], we, therefore, divide our sample into developed markets and emerging markets.…”
Section: Empirical Findingsmentioning
confidence: 99%